Peran Modal Sosial Dalam Meningkatkan Partisipasi Masyarakat Dalam Pemilihan TPQ (Studi Kasus Desa Dukuhseti Kecamatan Dukuhseti Kabupaten Pati Jawa Tengah) - Zahrotul Hikmah; Zulkipli Lessy (KOLONI, 2024)
This research takes the topic of social capital in selecting Al-Quran reading methods in Dukuhseti Village. In society, there are many types of Al-Qur'an learning methods that are very familiar, including: the Iqro', Ummi, Qiro'ati, Yanbu'a, Bahdadi, al-Karim methods and so on. In Dukuhseti Village, there are two methods used by the local community in the process of learning the Al-Qur'an, namely the Yanbu'a and Qiro'ati methods. With the development of the times, differences in views emerged in the local community towards these two methods which ultimately had an impact on the emergence of gaps between communities regarding each method of learning the Al-Qur'an. In general, both methods have similarities that offer ease and fluency in reading the Koran. This research aims to find out why in the Dukuhseti Village community the use of two Al-Qur'an learning methods emerged, namely Yanbu'a and Qiro'ati. This research uses descriptive qualitative methods. Data collection techniques using observation, interviews and documentation. Meanwhile, in analyzing the data, data reduction, data presentation, data verification and conclusion drawing are carried out. The theory used in this research is the theory of social capital (trust, norms and networks) proposed by Robert D. Putnam. The results of this research indicate that the social capital that influences the community in Dukuhseti Village in using Al-Qur'an learning methods is that the community's trust in learning institutions can increase students' interest in learning the Al-Qur'an. Then, people choose the Yanbu'a and Qiro'ati methods based on the influence of the surrounding environment. It's like there are non-binding regulations in the community to make it mandatory to register their children to study in the Yanbu'a and Qiro'ati methods.